PEMIKIRAN PENDIDIKAN KARAKTER ISLAMI DALAM PERSPEKTIF ABDUL MALIK FADJAR - M. Imam Mahdi; Farid Setiawan (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2021)
Education is a process of human investment, which is to prepare superior human resources. Islamic character education results from the mandate of national education to form people who believe and laugh at God Almighty, have personality, have a noble character, are healthy, skilled, knowledgeable, creative, and independent. With these values, it is hoped that the transformation process for students can be applied in everyday life. Educational thinkers in Indonesia have given many ideas and concepts of character education, one of which is Abdul Malik Fadjar, a practitioner in education. The moral crisis that hit Indonesia and the lack of superior resources for Muslims presents an offer of value from the figure of Abdul Malik Fadjar. Therefore, this study tries to understand and examine Islamic character education thought by Abdul Malik Fadjar. This research is expected to be an additional scientific treasure. This study uses an approach (library research) with direct data sources from the works of Abdul Malik Fadjar himself and a descriptive analysis model. The offer from the results of this study are: (1) according to Abdul Malik Fadjar, human investment education is not limited to cultural heritage but to prepare superior human resources for the challenges of globalization; (2) the values of integrated human character from divinity and humanity as well as the value of science and technology skills; (3) the curriculum content must have the principle of integrity; (4) the style of thinking about Islamic character education by Abdul Malik Fadjar is religious-integrity.